2010
DOI: 10.14723/tmrsj.35.1
|View full text |Cite
|
Sign up to set email alerts
|

X-ray Photoelectron Spectroscopic Analyses on the Corrosion-Resistant W-Cr-Ni Alloys in 12 M HCl

Abstract: The high corrosion behavior of the sputter-deposited amorphous or/and nanocrystalline WCr-(4-15)Ni alloys was investigated by corrosion tests, electrochemical measurements and X-ray photoelectron spectroscopy (XPS) including angle-resolved measurements in 12 M HCl at 30 o C, open to air. Particular attention was paid to the effects of tungsten, chromium and nickel metals addition on the surface composition of the passive films formed on the ternary alloys which is related to the corrosion-resistant as well as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 10 publications
3
10
0
Order By: Relevance
“…The instrument used and conditions subjected for the sputter deposition of these two alloys were same as those described elsewhere (Bhattarai, 2009(Bhattarai, , 2010b(Bhattarai, and 2010c. The composition, apparent grain size and structure of the alloys were analyzed by EPMA and XRD, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The instrument used and conditions subjected for the sputter deposition of these two alloys were same as those described elsewhere (Bhattarai, 2009(Bhattarai, , 2010b(Bhattarai, and 2010c. The composition, apparent grain size and structure of the alloys were analyzed by EPMA and XRD, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…It was found that the apparent grain size of the W-42Cr-5Ni, Cr10Zr-10W alloys including tungsten, chromium, nickel and zirconium metals was found to be about 3.5, 29, 20, 40, 19 and 24 nm, respectively. Accordingly, the W-42Cr-5Ni and Cr-10Zr-10W alloys were characterized as the mixture of nanocrystalline and amorphous, and a nanocrystalline structures having the apparent grain size of 3.5 nm (Bhattarai 2009 and2010b) and 29 nm (Bhattarai 2010c andBhattarai 2011a), respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that the high corrosion resistance of the sputterdeposited binary and ternary tungsten based alloys in 12 M HCl was based on the formation of new passive double oxyhydroxide films of tetravalent tungsten and alloyconstituting cations (Bhattarai 1998(Bhattarai , 2010Bhattarai et al 1995Bhattarai et al , 1997Bhattarai et al b, 1998. The tetravalent tungsten was the main oxidation state of tungsten for these tungstenbased binary alloys at +0.2 V (SCE) or lower potentials, while the hexavalent tungsten is the main oxidation state of tungsten at +0.4 V (SCE) or higher potentials in hydrochloric acid solutions.…”
Section: Introductionmentioning
confidence: 99%